THE EU NORMATIVE POLICY TOWARDS THIRD STATES: TURKEY AS A CASE STUDY - ALI, OMRAN OMER (Journal of Duhok University, 2019)
Since 1980s, promotion of principles of democracy has been a main element of the EU’s external policy in dealing with third countries. This research analyses the EU's external policy regarding the support of democratic and human rights principles, as well as it explores the extent to which the EU is considered to be a promoter of normative principles towards ‘third countries’ in general and Turkey in particular. It attempts to provide an academic answer to the question of ‘To what extent does EU foreign policy have an impact upon the promotion of democracy and human rights in Turkey? It argues that the EU has used the conditionality approach and Copenhagen Criteria as the basis for exerting impact on the Turkish reform process in guaranteeing democracy, human rights and fundamental freedoms in line with the EU standards. It concludes that despite the fact that the EU could have used more effective measures in order to produce a better outcome with respect to the Turkish reform process; the EU has played an important role in stimulating political and legal changes in Turkey since 1999.